Climate, energy, and water : managing trade-offs, seizing opportunities - Pittock, Jamie; Hussey, Karen; Dovers, Stephen (Cambridge : Cambridge University Press, 2015)
With the global population expected to reach nine billion by 2050, our capacity to provide enough food, water and energy relies on our understanding and management of the complex interdependencies in the climate-energy-water nexus. This book presents a comprehensive and up-to-date analysis of the interdependencies between these sectors and the knock-on consequences of those interactions for other sectors, such as food production and biodiversity conservation. The interdisciplinary nature of the book across the three sectors of climate, energy and water means that it will be valuable for advanced students, researchers and policymakers across a broad range of fields, including environmental/energy/water/climate policy, environmental economics, climate science, hydrology, ecology and geography.
11. Cross-sectoral governance of the climate, energy and water sectors: A'Rubik's cube' analysis of cross-sectoral co-ordination / Karen Hussey -- 12. Regulation of the nexus / Jacqueline Peel -- 13. Climate, energy and water: the potential roles and limitations of markets / Neil Byron -- 14. Strategies to mainstream climate change, energy, water and food security nexus knowledge and skills / Georges Dyer -- 15. A nexus of nexuses: systemic governance for climate response / Philip Wallis -- 16. Integrated modelling of the energy-water nexus in the American West / Vince C. Tidwell -- 17. Biodiversity and the climate, energy and water nexus / Jamie Pittock -- 18. Consumers, food supply chain and the nexus / Jakob Lundberg -- 19. Future prospects in climate, energy and water research and policy / Stephen Dovers.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Climate change mitigation; Power resources -- Management; Water-supply -- Management